Prevalência, distribuição espacial e fatores associados à infecção por toxoplasma gondii em bovinos do stio histórico e patrimônio cultural Kalunga, estado de Goiás, Brasil - Gomes, Daniella Ferreira Cordeiro (2020)
The Historical Site and Cultural Heritage Kalunga (HSCHK), located in the Chapada dos Veadeiros region, in the Cerrado of Goiás, is the largest remaining quilombo community in Brazil. Although subsistence farming is the main local activity, the animal health conditions of the cattle herd for important zoonosis, such as toxoplasmosis, are unknown. The study aimed to determine seroprevalence, spatial distribution and risk factors associated with infection by T. gondii in the bovine herd of the Kalunga community. The HSCHK was divided into five macro-regions, from which 1,533 samples of bovine blood serum were obtained. The search for anti-T. gondii antibodies were carried out using the indirect immunofluorescence reaction, establishing as a cut-off point ≥64. The risk factors associated with the infection were assessed by univariate analysis and logistic regression. Anti-T.gondii antibodies were identified in 8.93% (137/1533) of cattle from all macro-regions, with outbreaks in 49.6% (66/133) of herds. The factors associated with infection by T. gondii were: number of animals in the herd (up to ten animals, OR: 30.56), purchase of cattle (animals older than 12 months, OR: 2.57), age group of animals (zero to 24 months, OR: 1.95) and average annual temperature (28.5°C to 31.1°C, OR: 1.48). T. gondii infection in cattle is prevalent in all regions of the Kalunga community, requiring health education actions to prevent the disease in human and animal populations.